2020
DOI: 10.1590/1808-057x201909130
|View full text |Cite
|
Sign up to set email alerts
|

Investor sentiment and earnings management in Brazil

Abstract: This research analyzes whether there is a temporal association between investor sentiment and earnings management in Brazil. Several studies have investigated the determinants of earnings management, such as factors inside or external to companies and regulatory requirements, but few have considered personal factors, such as investor sentiment in Brazil. With this investigation, it was apparent from the findings that accruals quality is affected by investor sentiment. For participants in the Brazilian capital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
2
12
0
1
Order By: Relevance
“…This result is consistent with the theoretical developments (Kurov, 2010;Silvia & Iqbal, 2011;Vuchelen, 2004) and with recent empirical and experimental research (Cohen & Kudryavtsev, 2012;Menkhoff & Rebitzky, 2008;Zhang, 2019). Understanding this relationship is hugely desirable in Brazil, whose stock market is undeniably affected by investor sentiment (Lucchesi et al, 2015;Piccoli et al, 2018;Prates et al, 2019;Santana et al, 2020;Xavier & Machado, 2017;Yoshinaga & Castro, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result is consistent with the theoretical developments (Kurov, 2010;Silvia & Iqbal, 2011;Vuchelen, 2004) and with recent empirical and experimental research (Cohen & Kudryavtsev, 2012;Menkhoff & Rebitzky, 2008;Zhang, 2019). Understanding this relationship is hugely desirable in Brazil, whose stock market is undeniably affected by investor sentiment (Lucchesi et al, 2015;Piccoli et al, 2018;Prates et al, 2019;Santana et al, 2020;Xavier & Machado, 2017;Yoshinaga & Castro, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Finally, some evidence indicates that investor sentiment also affects earnings management and, therefore, firm-level decisions. This occurs as accounting choices are much more than financial decisions and are subject to psychological biases (Santana et al, 2020). These characteristics imply the need for a greater understanding of the factors that affect Brazilian investor sentiment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In itself, this rational action about the non-rationality of the investor, predominantly emotional, may configure and result in biases (Taffler & Tuckett, 2010). Some studies published internationally and nationally have demonstrated the influence of investor sentiment on financial decisions (Baker & Wurgler, 2007;Yoshinaga, 2009) in the formation of overly optimistic or pessimistic accounting profit expectations by analysts and investors and how these profit forecasts affect the relation between investor sentiment and stock returns (Santana, Santos, Carvalho Júnior, & Martinez, 2020).…”
Section: Investor Sentimentmentioning
confidence: 99%
“…Besides this, managers can change the company's accounting policy to raise the optimism level about its future forecasts, changing investors' perception (Healy & Wahlen, 1999;Paulo, 2007). Studies such as those by Yu, Hagigi, and Stewart (2018), Du (2019), and Santana, Santos, Carvalho Júnior, and Martinez (2020) found a relationship between earnings management and investor perception.…”
Section: Introduction Introductionmentioning
confidence: 97%